Using Laboratory Models to Test Treatment: Morphine Reduces Dyspnea and Hypercapnic Ventilatory Response - Banzett, Robert B. (American Thoracic Society, 2011)
Rationale: Opioids are commonly used to relieve dyspnea, but clinical data are mixed and practice varies widely. Objectives: Evaluate the effect of morphine on dyspnea and ventilatory drive under well-controlled laboratory conditions. Methods: Six healthy volunteers received morphine (0.07 mg/kg) and placebo intravenously on separate days (randomized, blinded). We measured two responses to a CO(2) stimulus: (1) perceptual response (breathing discomfort; described by subjects as “air hunger”) induced by increasing partial pressure of end-tidal carbon dioxide (Pet(CO2)) during restricted ventilation, measured with a visual analog scale (range, “neutral” to “intolerable”); and (2) ventilatory response, measured in separate trials during unrestricted breathing. Measurements and Main Results: We determined the Pet(CO2) that produced a 60% breathing discomfort rating in each subject before morphine (median, 8.5 mm Hg above resting Pet(CO2)). At the same Pet(CO2) after morphine administration, median breathing discomfort was reduced by 65% of its pretreatment value; P < 0.001. Ventilation fell 28% at the same Pet(CO2); P < 0.01. The effect of morphine on breathing discomfort was not significantly correlated with the effect on ventilatory response. Placebo had no effect. Conclusions: (1) A moderate morphine dose produced substantial relief of laboratory dyspnea, with a smaller reduction of ventilation. (2) In contrast to an earlier laboratory model of breathing effort, this laboratory model of air hunger established a highly significant treatment effect consistent in magnitude with clinical studies of opioids. Laboratory studies require fewer subjects and enable physiological measurements that are difficult to make in a clinical setting. Within-subject comparison of the response to carefully controlled laboratory stimuli can be an efficient means to optimize treatments before clinical trials.